IMPLEMENTASI MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI PADA SISWA SMAN 7 MALANG TAHUN 2024 - Emilia Nanda Sartika; Ifan Andriado; Erin Rahma Wati Eka Putri; Fitria Azizah Salsabila; Dimas Aulia Rifqy; Deny Wahyu Apriyadi; Emilia Nanda Sartika; Ifan Andriado; Erin Rahma Wati Eka Putri; Fitria Azizah Salsabila; Dimas Aulia Rifqy (Universitas Negeri Malang, 2024)
This research aims to explain the application and cycle results of the make a match type cooperative learning model to improve learning outcomes in the Sociology subject for class X students at SMAN 7 Malang. This research uses the Classroom Action Research (PTK) method. The research subjects were class X-1 students of SMAN 7 Malang for the 2023/2024 academic year, totaling 34 children. In this classroom action research, it was carried out in two action cycles. Each action cycle consists of planning, implementing and reflecting on actions. The data collection process is obtained from observations and tests to measure student learning outcomes. Based on the data obtained after implementing actions in cycles I and II, it is proven that the application of the make a match type cooperative learning model can improve the learning outcomes of class X-1 students at SMAN 7 Malang in the subject of Sociology. This is shown by the student learning results in the pre-action, student learning completion only reached 29% with the number of students getting scores above the KKM as many as 10 students. Then it increased in cycle I, student learning completeness reached 57% with a classical average score of 67.5. In cycle 2, students' learning completion reached 77% with a classical average score of 77.49.